Can frequent precipitation moderate the impact of drought on peatmoss carbon uptake in northern peatlands?. Issue 1 (1st April 2014) - Nijp, Jelmer J.; Limpens, Juul; Metselaar, Klaas; van der Zee, Sjoerd E. A. T. M.; Berendse, Frank; Robroek, Bjorn J. M.
Summary: Northern peatlands represent a large global carbon store that can potentially be destabilized by summer water table drawdown. Precipitation can moderate the negative impacts of water table drawdown by rewetting peatmoss ( Sphagnum spp.), the ecosystem's key species. Yet, the frequency of such rewetting required for it to be effective remains unknown. We experimentally assessed the importance of precipitation frequency for Sphagnum water supply and carbon uptake during a stepwise decrease in water tables in a growth chamber. CO2 exchange and the water balance were measured for intact cores of three peatmoss species ( Sphagnum majus, Sphagnum balticum and Sphagnum fuscum ) representative of three hydrologically distinct peatland microhabitats (hollow, lawn and hummock) and expected to differ in their water table–precipitation relationships. Precipitation contributed significantly to peatmoss water supply when the water table was deep, demonstrating the importance of precipitation during drought. The ability to exploit transient resources was species‐specific; S. fuscum carbon uptake increased linearly with precipitation frequency for deep water tables, whereas carbon uptake by S. balticum and S. majus was depressed at intermediate precipitation frequencies. Our results highlight an important role for precipitation in carbon uptake by peatmosses. Yet, the potential to moderate the impact of drought is species‐specific and dependent on the temporal distribution of precipitation.